Implementasi Pembiayaan Murabahah pada Perbankan Syariah di Indonesia: Studi Literatur - Shalahuddin, Muhammad Abdurrahman; Fauziah, Nenden Silmi (Department of Islamic Economics Law, 2023)
This study tried to look at research related to Murabahah Contract Financing in Islamic Banking in Indonesia bycollecting sufficient information on murabahah contract financing, such as house, vehicle, and productive installments, such as investment and business working capital. This research method uses qualitative methods, namely literature research by collecting some previous research during the period 2020 (two thousand twenty) to 2022 (two thousand twenty-two) that have been published, journal articles related to murabahah contract financing were collected as many as 25 (twenty-five). The search for this document study is a scientific paper that is not a thesis through the google scholar website page and the help of Public or Perish software (POP) using the keyword